Multimodal assessment of signalized intersections. Considering the number of travellers. - Hunter, Brian; Wolfermann, Axel; Boltze, Manfred (My University, 2011)
The purpose of transportation networks is the efficient and sustainable movement of people and goods. However, established evaluation procedures commonly assess the traffic quality instead of the transport quality, i.e. they focus on vehicles instead of goods and travellers. Furthermore, the existing methodologies evaluate the quality of each transport mode separately and often neglect the role of bicycles and pedestrians. Recently, several methods have been proposed to consider transport networks from a multimodal perspective, which is an important step towards the transport quality evaluation in the context of sustainability. A transparent and objective evaluation methodology is needed which comprehensively considers all transport modes. The procedure introduced in this article is limited to the assessment of signalized intersections, but goes one step beyond the existing methods: the multimodal assessment considers the number of travellers of the different modes. A route importance factor is introduced to reflect the differing significance of the transport modes. A case study underlines the strengths of the procedure.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsmittel; Signalanlage; Multimodalität; Verkehrsqualität; Verkehrsmessung